Performance comparison of a 3-D printed fiber bragg grating (FBG) load cell sensor based on the influence of different infill density and pattern - Alias, M A; Ahmad, Harith; Thambiratnam, Kavintheran; Samion, Muhamad Zharif; Sa'ad, M S M; Lim, Kok Sing; Zulkifli, Mohd Zamani; Mahmoodin, Z; Bayang, Leonard; Ismail, M F (IEEE, 2024)
This study proposes a novel optical fiber Bragg grating (FBG)-based load cell sensor using 3-D printing technology. It explores the impact of the infill density and pattern on the FBG’s temperature and mechanical strain sensitivity. Two FBGs were used, one for strain measurement, FBG L, and the other for temperature compensation, FBG T. Conducted measurements show that the strain-sensitive FBG L and strain-free FBG T exhibited a similar average temperature sensitivity value of around 10.5 pm/◦C with a good linearity value of 99.92%. This will also allow the unstrained FBG T to effectively compensate for FBG L’s temperature changes during load measurement. Under varied load conditions, load cell sensors with lower infill density, such as 20%, displayed more significant average wavelength shift and increased strain sensitivities compared to those with higher infill density, such as 80%, due to having more voids and hollow sections within its actuator. This facilitates easier deformation, thus inducing more significant stretching on FBG L. Regarding the infill pattern, the gyroid pattern outperformed the tri-hexagon in both average wavelength shift and strain responses, showing its suitability for precise measurements under diverse loads. Therefore, this work demonstrates the critical role of the infill density and pattern in the performance of an efficient load cell sensor using FBGs.